PENGAMANAN SOAL UJIAN DENGAN BANTUAN PERANGKAT LUNAK AxCrypt - Sucipto Adisuwiryo (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2012)
An Examination is a way to represent one’s ability into a certain grade. That’s why, it is confidential. Only certain people have the autorization in accessing the document. The document needs to be protected whether it is saved in hardisk, external hardisk, usb flashdisk or ‘sent item’ in email. The protection can be done by transforming the document into a confidential document so it can’t be seen by others. The transformation is called encription. Otherwise, it is called decription for transforming document into inconfidential document.The AxCrypt Tool can be used to protect exam document by encripting and open the document by decripting using password and key-file. AxCrypt is usefull for protecting the exam document that is saved in public computer, sending the classified exam document using email interface, and making only certain coordinator and lecturer who is responsible for the document, can open dan read the document.